Chemical Modification of Sago Waste For Oil Absorbent - Hayatun Syamila, Ali (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Oil spill and sago bark are both waste result from human activities. The environmental impact caused by these two wastes is devastating. Most of oil sorbent used nowadays is synthetic. This type of sorbent will not degrade naturally and may cause secondary pollution. In this study, sago bark is chemically modified by esterification reaction to exhibit oleophilic property to absorb oil. The modification is done by reacting sago bark with palmitic acid. There are three modified sago bark produced formed this study, which are MSB 1, MSB 2, and MSB 3, with different amount of catalyst used. The oil sorbents synthesized were subjected to FT-IR, SEM, buoyancy, density, and hydrophobicity test to characterize the physical and chemical characteristics. The effectiveness of the three modified sago bark and unmodified sago bark to absorb oil was compared in term of water sorption, oil sorption, and both oil and water sorption capacity. The unmodified sago bark shows poor water resistance compare to modified sago bark. In term of oil sorption capacity, MSB I shows the highest sorption compared to SB, MSB 1, MSB 2, and MSB 3.